ISSUES OF IMPROVEMENT OF THE INSTITUTION OF ADVOCACY IN CRIMINAL PROCEEDINGS - Gulchehra Tulaganova (PT. Antis International Publisher, 2024)
General Background: The legal profession is undergoing significant transformations influenced by advancements in technology and the increasing need for efficient legal processes. Specific Background: This study addresses critical issues in enhancing the legal profession, specifically focusing on the provision of legal services by lawyers and the mandatory involvement of legal representation. It also explores the transition towards digitizing criminal proceedings and the expansion of electronic technologies in legal practice. Knowledge Gap: Despite ongoing reforms, there is a lack of comprehensive strategies for integrating digital advancements within the legal framework, particularly in criminal proceedings. Existing literature does not sufficiently address how to systematically implement these technologies or adapt legal practices accordingly. Aims: This article aims to provide actionable recommendations for improving the legal profession, incorporating electronic technologies in legal practices, and establishing new legal frameworks for electronic criminal proceedings. Results: The study suggests enhancing the role of lawyers in legal processes, emphasizing the necessity of digital integration at all stages of criminal proceedings, and expanding the use of electronic technologies by legal professionals. Additionally, it reviews international practices and highlights the need for new legal foundations to support electronic criminal proceedings. Novelty: This article offers a novel approach by combining insights from both local and international experiences to propose a framework for advancing the digitalization of legal processes. It uniquely contributes to the discourse by recommending specific legal and technological improvements based on comparative studies. Implications: The recommendations provided could significantly influence legal practice by improving efficiency and accessibility in criminal proceedings. They also offer a roadmap for policy-makers and legal professionals to adapt to technological changes, ensuring that legal services remain relevant and effective in a digital age.